The Influence of Liquidity, Solvency, and Activity Ratios on Profit Changes in Consumer Goods Companies Listed on the Indonesia Stock Exchange (IDX) - Waruwu, Lisman Putra Abadi; Palupiningtyas, Dyah (Journal of Business Management and Economic Development, 2025)
This study examines the effect of liquidity, solvency, and activity ratios on profit changes of consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2018-2022. Using purposive sampling, 30 companies were selected. Secondary data from financial statements was analyzed using multiple linear regression. The results show that current ratio (CR) and total asset turnover (TATO) have a significant positive effect, while debt-to-equity ratio (DER) has a significant negative effect on profit changes. These findings align with signaling theory and the DuPont model. The study contributes to financial ratio analysis research and offers practical implications for company management and investors in evaluating financial performance and making decisions. Future research should expand the sample, explore other ratios and variables, and examine different sectors.